The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1687-9856-2014-20
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine growth restriction and hypospadias: is there a connection?

Abstract: Hypospadias is one of the most common congenital malformations of the genitourinary tract in males. It is an incomplete fusion of urethral folds early in fetal development and may be associated with other malformations of the genital tract. The etiology is poorly understood and may be hormonal, genetic, or environmental, but most often is idiopathic or multifactorial. Among many possible risk factors identified, of particular importance is low birth weight, which is defined in various ways in the literature. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 81 publications
(79 reference statements)
0
19
0
14
Order By: Relevance
“…Within this classification, hypospadias severity is stratified in ascending categories based on the severity of this disease. However, studies of hypospadias may use different classifications to describe severity and often fail to characterize additional features of hypospadias such as the presence of chordee (Chen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Within this classification, hypospadias severity is stratified in ascending categories based on the severity of this disease. However, studies of hypospadias may use different classifications to describe severity and often fail to characterize additional features of hypospadias such as the presence of chordee (Chen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…10,11 A particular factor responsible has been shown to be intake of phytoestrogens and its deleterious effect on the development of male genital system. 4,5,8,9,12 We have attempted to supplement this hypothesis by correlating an increased maternal gestational vegetarian diet with increased prevalence of hypospadias n male babies. Similar studies done back in 2000 have shown that phytoestrogen intake does cause ill effects on the development of male genital system which may cause hypospadias.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence varies worldwide and different rising trends have been seen in different population groups. 3,4 Both genetic and environmental factors are believed to be responsible. [3][4][5] There has been a recent interest in understanding its relation to the maternal gestational factors.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, placental dysfunction may reduce nutrient transfer to the fetus, consequently contributing to restricted growth [56]. However, placental insufficiency after the critical developmental window that results in growth restriction would not cause hypospadias [53]. In Fig.…”
Section: Pregnancy and Birth Characteristicsmentioning
confidence: 99%
“…Placental dysfunction and androgen deficiency in early pregnancy have been proposed as shared causes of intrauterine growth restriction and hypospadias [46••, 49, 50]. Specifically, placental dysfunction may lead to inadequate production or transport of human chorionic gonadotropin, or other placenta-derived factors, which fail to stimulate appropriate fetal androgen production necessary for normal urethral closure [49][50][51][52][53] and potentially involved in somatic growth [54,55]. Additionally, placental dysfunction may reduce nutrient transfer to the fetus, consequently contributing to restricted growth [56].…”
Section: Pregnancy and Birth Characteristicsmentioning
confidence: 99%